Importance of applied science in training program design - Hoffman, J. R. (EWF Scientific Magazine, 2015)
The understanding of training program design is based upon a strong knowledge of scientific principle. It is the product of the basic sciences; biology, physics and chemistry, which are combined to an applied field of study such as exercise science that has additional specific emphasis in the study of physiology, biomechanics and biochemistry. The understanding of basic physiological response to exercise is an important aspect in the training of athletes and in providing the background to develop realistic training goals that can be achieved through effort and good coaching. An understanding of science provides us the ability to effectively evaluate the efficacy of various training paradigms and critically examine the broad spectrum of available ergogenic aids and nutritional supplements that are continuously being provided or suggested to athletes. In addition, understanding the applied sciences will allow the sport scientist and coach to better comprehend the physiological, psychological and biomechanical requirements necessary for success in sports and help develop selection criteria that maximizes the chance of athlete and team success.